Adsorptive conversion of nitrogen dioxide from etching vent gases over activated carbon. (3rd July 2018) - Fang, Mei-Ling; Wu, Ching-Yi; Chou, Ming-Shean
ABSTRACT: Some metal etching operations emit limited flow rates of waste gases with reddish-brown NO2 fume, which may cause visual and acidic-odor complaints, as well as negative health effects. In this study, tests were performed by passing caustic-treated waste gases vented from Al-etching operations through columns packed either with virgin or regenerated granular activated carbon (GAC) to test their adsorptive conversion performance of NO2 in the gases. The gases contained 5–55 ppm NO2 and acetic and nitric acids of below 3 ppm. Exhausted carbon was regenerated by scrubbing it with caustic solution and water, and dried for further adsorption tests. Results indicate that with an (empty bed residence time (EBRT) of 0.15 sec for the gas through the GAC-packed space, around 60% of the influent NO2 of 54 ppm could be removed, and 47% of the removed NO2 was converted by and desorbed from the carbon as NO. GAC used in the present study could be regenerated at least twice to restore its capacity for NO2 adsorption. Within EBRTs of 0.076–0.18 sec, the adsorptive conversion capacity was linearly varied with EBRT. In practice, with an EBRT of 0.20 sec, a conversion capacity of 0.80 kg NO2 (kg GAC) −1 with an influent NO2 of 40 ppm can be used as a basis for system design. Implications : Some metal etching operations emit waste gases with reddish-brown (yellow when diluted) NO2 fume which may cause visual and acidic-odor complaints, as well as negative health effects. This study provides a simple process for the adsorptive conversion of NO2 in caustic-treated waste gases vented from metal-etching operations through a GAC column. With an EBRT of 0.20 sec, a conversion capacity of 0.80 kg NO2 (kg GAC) −1 with an influent NO2 of 40 ppm can be used as a basis for system design. Saturated GAC can be regenerated at least twice by simply scrubbing it with aqueous caustic solution.